The Polyphenolics and Health Effects of Pomegranate - Nge, Sonya Titin; Martosupono, Martanto; Karwur, Ferry Fredy (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Pomegranate (Punica granatum L.) is a useful fruit which mostly consumed as fresh fruit and can also be used as a various of processed products. Reports proved pomegranate were beneficial to health. Polyphenolic compounds in pomegranate especially ellagitannin (hydrolyzed), anthocyanins, gallotannin,and ellagic acid can maintain oral hygiene, healthy skin from the effects of free radicals caused by UV radiation, has the ability to synthesize cholesterol, destroying free radicals in the human vascular system and can prevent prostate cancer. In vitro and in vivo test has shown the fruit is acting as anti diabetic drug, and hypolipidemic, anticarcinogenic, antibacterial, anti inflamation, and antiviral. This review presenting an overview about the bioactive compound contents, physiological and health function of the fruit.